2008
DOI: 10.1158/1078-0432.ccr-07-2060
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 Inhibition Down-Regulates Radiation-Induced Nuclear Factor-κB Activity Leading to Apoptosis in Breast Tumors

Abstract: Purpose: Novel strategies are needed to prevent the high mortality rates of several types of cancer.These high rates stem from tumor resistance to radiation therapy, which is thought to result from the induction of matrix metalloproteinases (MMP) and plasminogen activators. In the present study, we show that the modulation of MMP-9 expression, using adenoviral-mediated transfer of the antisense MMP-9 gene (MMP-9 adenoviral construct, Ad-MMP-9), affects breast cancer sensitivity to radiation. Experimental Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…Several reports have shown that Fas/Fasligand system is enhanced in the cancer cells treated with anti-cancer chemotherapeutic agents 57. Apart from chemotherapeutic agents, down regulation of MMPs was reported to induce Fas-mediated apoptosis and inhibit tumor progression in lung cancer58 and breast cancer 59. Similarly, in the present study the expressions of Fas-ligand as well as its receptor were enhanced in the siRNA plasmid transfected prostate cancer cells, providing further insight to the earlier reports.…”
Section: Discussionsupporting
confidence: 87%
“…Several reports have shown that Fas/Fasligand system is enhanced in the cancer cells treated with anti-cancer chemotherapeutic agents 57. Apart from chemotherapeutic agents, down regulation of MMPs was reported to induce Fas-mediated apoptosis and inhibit tumor progression in lung cancer58 and breast cancer 59. Similarly, in the present study the expressions of Fas-ligand as well as its receptor were enhanced in the siRNA plasmid transfected prostate cancer cells, providing further insight to the earlier reports.…”
Section: Discussionsupporting
confidence: 87%
“…The over expression of uPA, uPAR and cathepsin B by radiation has been detected in various malignancies, including those in hepatocellular [22], rectal [23] and breast [24] cancer. Most of the cellular responses modulated by these proteolytic networks, including migration, cellular adhesion, differentiation, proliferation and angiogenesis require transmembrane signaling, which is mediated by direct contacts of these proteolytic networks with a variety of extracellular proteins and membrane receptors.…”
Section: Discussionmentioning
confidence: 99%
“…HGF induces VEGF expression in cancer cells and is a key switch for turning on angiogenesis [61]. It has been reported that adenovirus-mediated inhibition of MMP-9 (Ad-MMP-9) with radiotherapy decreased levels of NF-κB and activator protein 1, both of which contribute to the radioresistance of MDA-MB-231 cells in vitro and in vivo ; treatment with Ad-MMP-9 plus radiation completely regressed tumor growth in orthotopic breast cancer model [62]. Our present results of reduction of MMP-9 in the radiotherapy patients who received EGCG may contribute to the decrease in NF-κB level and inhibition of proliferation in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%